State capitalism in Eurasia - Spechler, Martin C.; Ahrens, Joachim; Hoen, Herman Willem (World Scientific Pub., 2017)
This is the first book to specify the type of economic system that has arisen in Central Asia, replacing the simplistic ideas of "petro-state" or "resource dependent." The book presents three types of state capitalism now established in the former Soviet Union states of Eurasia -- crony, dual-sector, and predatory capitalism. It provides first-hand research based on extensive interviewing in the native languages in five of the six. From the political economic perspective, it surveys the source of resources for these authoritarian regimes, their decision-making, and the disposition of government funds, including corruption.